Determination of Financial Sustainability in Indian Banking Industry - Thangam, Mahila Vasanthi; Helina, Dr. S. Thanga; Sudha, A. G. (International Journal of Psychosocial Rehabilitation, 2020)
Financial sustainability means the ability to maintain the financial health at a certain rate or level. It has a close relationship with the financial efficiency of any financial institutions like banks which mean provision of highest quality financial services at the lowest possible cost. So the overall growth of any country’s economy depends to an exquisite quantity on the financial health of its banking system. This research has its focus on analysis and measurement of the overall health of banks in India. The present study is an analytical research purely based on secondary data, which has been taken from the published annual reports from the official reports of banks, data obtained from CMIE database, Statistical tables published by Reserve Bank of India for the period of eight years from 2011-12 to 2018-19 of 20 Public sector banks and 22 Private sector banks, five banks from each sector have been taken into account using stratified random sampling technique. Tools viz. basic ratio analysis, average, co efficient of variation, trend, and CRAMEL, Bankometer, and Spearman Rank correlation and students t test were used for the analysis. It may be generalized that the private sector banks are performing better than the public sector banks. The study also recommends that the Bankometer can be used to study the financial health of banks rather all other tools as it pinpoints the areas of strength and weaknesses of banks.